الاتجاهات الحديثة لخدمات المعلومات الالكترونية في المكتبات: بين الواقع والمأمول - بوعافية, السعيد (Sciences humaines, 2014)
إن التطورات الجذرية التي تحدث في مجال صناعة وخدمات المعلومات توفر معطيات ذات أثار عميقة لم يشهدها الإنسان أو متخذ القرار من قبل، ويميز وضع  المكتبات ومراكز المعلومات في أي مجتمع  بأنه يقع  وسط  بؤرة  أي  نشاط  اجتماعي أو اقتصادي أو علمي في ذلك المجتمع، والمكتبات لا يمكن أن تنعزل عن المعرفة بحكم أنها جوهر ما تفعله،وبذلك تظل أكثر المؤسسات في المجتمع تأثرا بأي تغير فيه، وتهدف هذه الدراسة إلى تقديم الإطار النظري حول خدمات المعلومات الالكترونية،واستشراف مستقبلها وكيفية تطويرها كتحدي لمؤسسات المعلومات في الألفية الثالثة   The basic progress in the field of information services and it’s industry gives more data that have deep influence haven’t seen before, and the location of libraries and information centers in any society is characterized by being taking position in the middle of a social, economical or a scientific activity in that society, so libraries can’t be isolated from knowledge because its core activity and this factor gives libraries the most importance and and influence in any society, so library is exposed to any change may touch the society itself. The objective of this study is to give the theoretical frame about digital information services, and a view about its future and how to give it a push as challenge for the information institution of the third milliunum.